The effectiveness of a 10-week family-focused e-Health healthy lifestyle program for school-aged children with overweight or obesity: a randomised control trial - Diana Zhu; Aimee L. Dordevic; Simone Gibson; Zoe E. Davidson (BMC Public Health)
Abstract Background Electronic health (e-Health) interventions may increase effectiveness and address limitations of conventional in-person childhood obesity treatment programs. This study evaluates the effectiveness of a 10-week e-Health (web-based) healthy lifestyle program for school-aged children with overweight/obesity. Methods In this randomised control trial (RCT), families with children aged 7–13 years with overweight/obesity (body mass index, BMI ≥ 85th percentile), living in Victoria, Australia, were recruited. Families were randomised to intervention or waitlist control and received the 10-week web-based program. The primary outcome was the change in children’s BMI z-score over 10 weeks. Other outcomes included change in children’s waist circumference, dietary intake, physical activity, and quality of life over 10 weeks. Results Of 148 children (125 families) recruited, 102 children (85 families) completed the RCT. A significant decrease in children’s BMI z-scores was observed in the intervention compared to the control group over 10 weeks (mean difference 0.11; 95% CI, 0.02–0.20). The web-based program was also effective in improving children’s quality of life and lifestyle behaviour changes over 10 weeks. In the intervention group, there was a significant increase in children’s quality of life scores (intervention versus control: median change (IQR) = 11 (3, 17) versus 1 (-3, 7); p = 0.034), overall diet quality scores (6 (2, 10) versus 2 (-3, 5); p < 0.001), and daily physical activity levels (5.2 (-2.6, 12.8) versus − 0.2 (-8.2, 4.5); p = 0.022) compared to the control group. Conclusions A web-based healthy lifestyle program effectively improved short-term health-related outcomes in children with overweight/obesity. Further research is needed to identify determinants of program effectiveness, evaluate sustained effects, and equitably tailor childhood obesity e-Health interventions to diverse populations. Trial registration This study was registered with the Australian New Zealand Clinical Trial Registry (ACTRN12621001762842) on November 11, 2021, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=383053 .